Pengembangan Kreativitas Dan Bakat Siswa Melalui ekstrakurikuler Seni Tari Di SD Negeri 2 Paras - Widatik, Sri; Drs. Suwarno, Drs. Suwarno SH., M.Pd (2017)
Creativity is the ability to express themselves creatively, although every student has the talent and creativity in the field and in the different levels. Aptitude is an innate ability, as the potential that still need to be developed and trained to be realized. With the development of gifted students can work alone and able to collaborate with others. Extracurricular activity helps develop students according to the needs, potential, talents, and interests. oughextracurricular, learners can establish the personality development of students tend to evolve to choose a particular path. The art of dance is one of the very old culture and insensitive to age and is one form of human expression on the environment and life. This study aims to describe the development of creativity and talent of students through extracurricular dance in SD Negeri 2 Paras. This study used a qualitative approach with descriptive qualitative research design. This research was conducted in SD Negeri 2 Paras and Gayatri Studio from January 2016 to February 2017. Data collection techniques used were observation, interviews, and documentation. Data analysis included data reduction, data presentation, and conclusion. And test the validity of the data by triangulation of sources and techniques. Based on the results of this study concluded that efforts of teachers to develop creativity and talent by exercise, discuss, and then displayed. By way practiced or actualized in a particular activity or event, the students more active in participating in extracurricular activities of dance.Keywords: Creativity, talent, Extracurricular, Dance Art.